Nghiên cứu sự tạo phức của một số ion kim loại với axetylaxeton bằng phương pháp phân tích nhiệt - Huỳnh, Lê Văn; Tuyết Mai, Trần Thị (Vietnam Journal of Chemistry, 2015)
The complex is made up of metal ions with acetylacetone are increasingly widely used in many fields such as extraction capability, thin film fabrication, electronic luminescence materials, catalyst ... In normal conditions acetylacetone molecules always exist two enol and ketone, depending on the pH of the reaction environment ketone or enol form dominates. Because the mobility of the hydrogen atoms in the enol group and the possibility for electrons in the oxygen atom of the ketone group, should have the ability to create complex acetylacetone very good with some metal ion coordination links. This paper is the result tucua study the structure of the complex, which is made by metal ions Al(III), Co(II), Ni(II) and Cu(II) with acetyl acetone by thermal analysis methods. The research results are scientific basis for the application of complex in the production the process of technology.